Assessment of banana (Musa xparadisiaca) clones of AAB group based on stability and adaptation - RAJAMONY, L; GEORGE, K C; ANITHA, N; RADHAKRISHNAN, T C (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1982-91 to assess 21 banana (Musa xparadisiaca L) clones of AAB group based on their stability and adaptation. The clones represented 4 different gepgraphic locations, viz eastern Australia, north-east India, south India and Zanzibar, overall performance was judged on the basis of yield aLtributes like weight of bunch, number of hands, number of fingers; quality attributes like total soluble solids; and reactions towards the yield-limiting biotic stresses like rhizome weevil(Cosmopolites sordidus Germer.), banana nematode (Radopholus similis Cobb.) and sigatoka leaf-spot (Mycosphaerella musicola Leach ex Mulder). Among the 27 dones, ’Mysore Poovan’ and ’Mulaikali’ proved the most established and adapted ones. Among the. others, ’Chinali’, ’Martaban’, ’Krishnavazhai’, ’Kodappanillakunnan’, ’Dhudsagar’ and ’Mottapoovan’ were foundÂ more stable, In the plantain subgroup, ’Mysore Ethan’,’Nendran’ and ’Myndoli’ Were superior to others. ’Mysore Poovan’ WaS also found reistant to rhizome weevil. Clones "Thiruvananthapurum’, ’Mysore Ethan’ andÂ ’Padalimoongil’ showed moderate multiple resistance equally 10 rhizome weevil, banana nematode and sigatoka leaf-spot Â